Key features for forest bathing development: A Q-methodology study applied in Italy - Sofia Baldessari; Alessandro Paletto; Giorgia Di Domenico; Valerio Di Stefano; Sandro Sacchelli (Journal of Forest Science)
Forest bathing is gaining attention for its health and well-being benefits, leading to growing interest among academics, policymakers, and practitioners. While most studies have focused on its physiological and psychological effects, less is known about how different stakeholders perceive the characteristics that make forest bathing effective and meaningful. This study explored expert and non-expert perspectives on forest bathing in Italy through the Q-methodology, aiming to identify shared and divergent views on key aspects such as site features, accessibility, and perceived benefits. The results highlighted four distinct viewpoints: a scientific-health-oriented perspective emphasising medical efficacy (mainly experts); a preference for more naturalness and ecological integrity (mainly non-experts); a possible socio-economic opportunity (mainly non-experts); and a preference for a more managed forest environment with supporting structures (mainly experts). Despite differences, consensus emerged on several points, including the cultural and physical relevance of forest bathing and the importance of inclusive accessibility while preserving low-impact environments. The findings highlighted the potential of Q-methodology to capture the plurality of stakeholder voices, offering a basis for more inclusive planning and policy development in the context of nature-based well-being initiatives.